Representações dos espaços rural e urbano na ficção de Adonias Filho - Almeida, Maria Fernanda Arcanjo de (2014)
This research has as theme the representation of rural and urban spaces in two specific novels of the author Adonias Filho: Corpo vivo, published in 1952, and O forte, published in 1962. Notedly the work of the author in question remains devoid of further study, despite its greatness, quest through space's reading highlight his novelistic. The choice of space-themed is due to two factors: 1) such a thematic, although come calling critical attention in recent years, is still relegated to the background, especially when compared to other elements of the narrative, like time and personages; 2) In the adonianas narratives the space exerts primary function isn‟t just décor, backdrop for the actions, thus becoming like a kind of character with enough action‟s force to influence the fate of beings of wefts. The modalities of space chosen in such a study ( rural and urban) , despite present themselves like two sides of the same coin, consecrate great differences between them making thus plausible the analysis of conflicts and tensions that underlie the spaces of the narratives examined here. The research in question is characterized as qualitative in which written sources, especially books, journals and digital documents are used. The interdisciplinarity is another brand in present study, since space is a category that allows the combination of various areas of knowledge. Thus, the theoretical scope presented is eclectic and encompasses both literary theory as other fields of the humanities, like the cultural geography and history.